Oregon indemnity [electronic resource] : claim of chief factors and chief traders of the Hudson's Bay Company thereto, as partners under Treaty of 1846. - McLeod, Malcolm, 1821-1899. ([Ottawa : s.n.], 1892)
Table. Manuscript annotations. Attributed to Malcolm McLeod --A bibliography of British Columbia : laying the foundations, 1849-1899 / by Barbara J. Lowther. Includes index. Electronic reproduction. Mode of access: Internet. 44